Quiz (1 point)
Prove that:
result of appending (Python object: [ entry "__class_name__": "Dog", [ ] ]) to [ ] = [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ]
The following properties may be helpful:
- result of appending y to xs = reverse of [ y, reverse of xs ]
- reverse of [ ] = [ ]
- reverse of [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ] = [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ]
if reverse of [ ] = [ ], then [ Python object: [ entry "__class_name__": "Dog", [ ] ], reverse of [ ] ] = [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ]
if [ Python object: [ entry "__class_name__": "Dog", [ ] ], reverse of [ ] ] = [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ], then reverse of [ Python object: [ entry "__class_name__": "Dog", [ ] ], reverse of [ ] ] = reverse of [ Python object: [ entry "__class_name__": "Dog", [ ] ], [ ] ]
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.